Acute appendicitis: standard treatment or laparoscopic surgery? - Krähenbühl, Lukas 1961-; Frei, Edgar; Klaiber, Christian; Büchler, Markus W. 1955- (Karger, 1998)
This handy volume reviews the current approaches to acute appendicitis, appendectomy being the most commonly performed emergency surgical procedure in the western world. The benefits and costs of open versus laparoscopic appendectomy are discussed by international specialists in the field. Exact diagnosis on right iliac fossa pain is still difficult, especially in children, young females, older patients and during pregnancy. It is in these cases that the laparoscopic approach may be most beneficial, both in terms of diagnosis and surgery, whereas the open procedure is still the gold standard in patients with a clear diagnosis of appendicitis. However, laparoscopic surgery is at least as effective, although more expensive and complicated to perform. Furthermore, in terms of the wound infection rate, the laparoscopic method has proven to be more effective. This book is of interest for general and laparoscopic surgeons, as well as for emergency doctors, gastroenterologists, gynecologists and doctors with an interest in epidemiology
International Meeting, Bern, May 1997 ; open compared to laparoscopic appendectomy: Where do we stand today?
Keywords: Surgery; Gastroenterology; Endoscopy; Gynecology; Ultrasound; Minimal-invasive Chirurgie; Appendektomie; Aufsatzsammlung